Effect of high sedimentation rates on surface sediment dynamics and mangrove growth in the Porong River, Indonesia. Issue 1 (15th June 2016) - Sidik, Frida; Neil, David; Lovelock, Catherine E.
Abstract: Large quantities of mud from the LUSI (Lumpur Sidoarjo) volcano in northeastern Java have been channeled to the sea causing high rates of sediment delivery to the mouth of the Porong River, which has a cover of natural and planted mangroves. This study investigated how the high rates of sediment delivery affected vertical accretion, surface elevation change and the growth of Avicennia sp., the dominant mangrove species in the region. During our observations in 2010–2011 (4–5 years after the initial volcanic eruption), very high rates of sedimentation in the forests at the mouth of the river gave rise to high vertical accretion of over 10 cm y − 1 . The high sedimentation rates not only resulted in reduced growth of Avicennia sp. mangrove trees at the two study sites at the Porong River mouth, but also gave rise to high soil surface elevation gains. Highlights: Very high rates of sedimentation occur in the mangrove forests at the mouth of the Porong River. Mangroves in the Porong River can adapt to high sedimentation, exceeding tolerances published in literature. High rates of sediment delivery significantly affect vertical accretion and soil surface elevation gains.